Pendidikan Karakter Dalam Tafsir Nusantara: Studi Tematik Kitab Tafsir Al-Azhar Karya Hamka - Mukhlasin, Ahmad; Maragustam Siregar (Pusat Riset dan Inovasi Nasional, 2025)
This paper investigates the values of character education embedded in Tafsir al-Azhar by Haji Abdul Malik Karim Amrullah (Hamka), an influential work representing the tradition of Nusantara exegesis (tafsir Nusantara). The research aims to identify and analyze the relevance of character values that Hamka contextualized within the Indonesian socio-cultural environment. The study utilizes the maudhu‘i (thematic) approach to Qur'anic exegesis, focusing on verses pertaining to the formation of human character. This methodology allows for a comprehensive exploration of universal moral values interpreted by Hamka. The findings indicate that Hamka places strong emphasis on the necessity of several core values as the foundation for the character of a virtuous and faithful individual. These crucial values include honesty (kejujuran), trustworthiness (amanah), responsibility, tolerance, and patriotism/love for the homeland. Hamka’s interpretation consistently links these spiritual and moral values with the local Indonesian context, reflecting the text's adabi ijtima‘i (socio-literary) characteristic. Furthermore, the study highlights that Hamka advocates for an integrated education system that rejects a purely cognitive focus, instead emphasizing the essential balance between intellect and spirituality to produce morally sound individuals. The educational concepts proposed by Hamka are highly relevant to the contemporary needs of Islamic education, particularly in addressing the pervasive challenges of moral globalization and value disorientation in the modern era. His perspective aligns well with modern educational paradigms, including the principles of the Profile of Pancasila Students (Profil Pelajar Pancasila) in Indonesia, which seek to integrate faith, knowledge, and noble character. Thus, Hamka’s Tafsir al-Azhar serves as a vital moral guide and a robust framework for developing a moderate, humanist, and nationally conscious Islamic character education system in modern Indonesia